2019
DOI: 10.1111/fwb.13437
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota associated with the skin, gills, and gut of the fish Parachondrostoma toxostoma from the Rhône basin

Abstract: 1. The close relationships between hosts and their microbiota underlie the current concept of holobionts. This biological entity enlarges our perception of the genomic diversity supported by individuals/species and the potential abilities of hosts to respond to the environment.2. We investigated a total of 54 specimens of the sofie fish Parachrondrostoma toxostoma (Pt) for the taxonomic and functional composition of microbiota associated with the skin, gills, and gut tissues. Five wild populations from the Ard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Regarding diversity, gill mucus harbored a lower alpha diversity, compared to skin mucus and water bacterial communities. Other freshwater or seawater fish species display a similar trend, with a lower diversity in gill mucus compared to the skin mucus [ 15 , 64 , 88 ]. Moreover, we found that sparid skin and gill mucus are also highly species-specific, both in terms of diversity and composition, as previously reported in several other fish families such as Chaetodontidae, Serranidae, Labridae or Mullidae [ 23 , 24 , 64 , 82 , 89 ].…”
Section: Discussionmentioning
confidence: 98%
“…Regarding diversity, gill mucus harbored a lower alpha diversity, compared to skin mucus and water bacterial communities. Other freshwater or seawater fish species display a similar trend, with a lower diversity in gill mucus compared to the skin mucus [ 15 , 64 , 88 ]. Moreover, we found that sparid skin and gill mucus are also highly species-specific, both in terms of diversity and composition, as previously reported in several other fish families such as Chaetodontidae, Serranidae, Labridae or Mullidae [ 23 , 24 , 64 , 82 , 89 ].…”
Section: Discussionmentioning
confidence: 98%
“…gills that had increased total AA biosynthesis. Enrichment of AA metabolism in sh skin has been related to metabolic pathways involved in the activation of immune responses (Guivier et al 2020) and, thus, could of relevance to defence mechanisms against pathogens colonising the skin. The highest relative abundances of AA biosynthesis were observed for isoleucine, methionine, lysine, and arginine.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, gut microbiota play a central role in digestion and the health status of their host [8]. Studies on fish microbiota have increased these last years, showing that individual factors may affect the bacterial community, such as host sex [9] or development stage [10]. Environmental factors may also influence microbiota [11], and diet seems to be one of the major factors affecting its composition [9,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on fish microbiota have increased these last years, showing that individual factors may affect the bacterial community, such as host sex [9] or development stage [10]. Environmental factors may also influence microbiota [11], and diet seems to be one of the major factors affecting its composition [9,[12][13][14][15][16]. Indeed, Fishes 2022, 7, 312 2 of 14 several studies have shown that in rearing conditions, the intestinal microbiota is fooddependent, and this could be in terms of both alpha (i.e., within each sample) and beta diversity (i.e., between samples) [17,18].…”
Section: Introductionmentioning
confidence: 99%